2009
DOI: 10.1111/j.1365-294x.2009.04218.x
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected panmixia in a long‐lived, deep‐sea fish with well‐defined spawning habitat and relatively low fecundity

Abstract: The marine environment presents particular challenges for our understanding of the factors that determine gene flow and consequent population structure. For marine fish, various aspects of life history have been considered important in an environment with few physical barriers, but dominated by current patterns, often varying with depth. These factors include the abundance and longevity of larval stages, typically more susceptible to movement along current paths. It also includes adult body size, fecundity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 104 publications
7
50
2
Order By: Relevance
“…Flow patterns of tidal or oceanic currents may also contribute to the genetic isolation among global populations by hindering dispersal (22,23,28,58,59). For example, there were no significant F ST values between populations from the North Sea and a connected Danish inland fjord, yet populations from the Irish Sea and the adjacent North Sea showed significant differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow patterns of tidal or oceanic currents may also contribute to the genetic isolation among global populations by hindering dispersal (22,23,28,58,59). For example, there were no significant F ST values between populations from the North Sea and a connected Danish inland fjord, yet populations from the Irish Sea and the adjacent North Sea showed significant differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Population genetic surveys using high-resolution markers that allow differentiation among individuals, are greatly improving our understanding of the mechanisms that cause genetic diversity within and gene flow between populations (20). To date, population genetic studies of high-dispersal organisms in the marine environment have largely focused on pelagic or benthic animals with planktonic larval stages (21)(22)(23)(24). Population genetic structuring of planktonic microorganisms has been much less explored due to difficulties with species delineation and lack of finescale genetic markers for these organisms (25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Other recent studies using microsatellite loci have found populations in the North Atlantic to be genetically panmictic (Palm et al, 2009;White et al, 2009). For marine species occupying a large range of environments and with large effective population sizes, neutral loci may exhibit little divergence despite fairly limited gene flow, whereas loci under strong selection may display a high degree of differentiation (White et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to be able to draw on ecological and life history data to assess when apparent genetic panmixia may be consistent with demographic dependence. Long-range or distribution-wide panmixia has been reported fairly rarely (for example, Garber et al, 2005;Tolley et al, 2005;Palm et al, 2009;White et al, 2009), but was the default expectation for pelagic marine fish species until various studies demonstrated patterns of population structure, sometimes over small geographic scales (for example, Knutsen et al, 2003). In this study, we address the general question of what life history characteristics may lead to panmixia by investigating the population genetics of a deep-sea fish, the blue hake (Antimora rostrata).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been some unexpected results. For example, the orange roughy ( Hoplostethus atlanticus ) has life -history characteristics that could promote population structure (for example, long life, comparatively low fecundity and larval duration), but genetic data suggest no structure in the North Atlantic study area (White et al 2009 ;S. Stefanni, unpublished observations).…”
Section: Population S Tructurementioning
confidence: 99%